Determination of Transport Routes using the Saving Matrix Method at PT XYZ - Anisa Natasari; Hilal Ali Azzim; Fahrul Arifin; Muchammad Fauzi (Green Publisher Indonesia, 2021)
PT XYZ is a company engaged in manufacturing that produces electronic components and installation services for these components. In this study, the company will send components and help install them in nine locations in Sumatra. The analysis of determining distribution routes uses the saving matrix method. The results of the analysis using the saving matrix method show that the original distribution distance of 9926 kilometers can be reduced to 2937.7 kilometers, which means that the distance can be shortened and more efficient by 70% or around 6988.3 kilometers. The original cost was Rp. 54,386 .000 down to Rp. 16,716,000 Thus there is a distribution channel savings of Rp. 37,670,000 or about 69.2%.